THE HABITAT AND ECOLOGICAL NICHES OF STAPHYLOCOCCI: A SCIENTIFIC REVIEW (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
In mammals, staphylococci physiologically colonize the skin, sebaceous and sweat glands, and the mucous membranes of the nose, oropharynx, intestines, and urogenital tract [2,6,10,16]. Staphylococcus aureus permanently or transiently colonizes approximately 20-30% of the human population, predominantly in the nares and on the skin [1,10,14,16].